Strategies to Build a Branding School in Efforts to Improve the Competitiveness of Islamic Education Institutions - Riza Rizkiyah; Istikomah Istikomah; Nurdyansyah Nurdyansyah (International Consortium of Education and Culture Research Studies, 2020)
The aim of this research is to find out the importance of the strategy of building a branding school and its effect on competitiveness with other Islamic educational institutions. This research belongs to the type of library research, where researchers deal directly with existing data not through field research, by examining books, journals and other data deemed relevant. So it can be concluded that in the strategy of building a branding school analysis is needed on what factors cause the branding school, then arrange the steps in building a branding school, and the impact or benefits of branding school on competitiveness.